2012
DOI: 10.1111/j.1742-481x.2012.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for foot ulceration in a general haemodialysis population

Abstract: It is well documented that diabetic foot ulceration contributes to increased morbidity and mortality associated with renal replacement therapy. Much less is known about the risk of foot ulceration and lower limb amputation in the non-diabetic dialysis population. The aim of this study was to determine if the prevalence of risks factors for lower limb amputation in a stable haemodialysis population was greater in the diabetic cohort compared with the non-diabetic cohort. The study design is a prospective observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 27 publications
(33 reference statements)
4
24
2
2
Order By: Relevance
“…The authors found an increased association of CVD and mortality in diabetic patients with FU in comparison to those without FU. Interestingly, a recent study advocated a higher incidence of risk factors (PAD and peripheral neuropathy) for FU among HD patients [13]. In Qatar, an earlier report from our center identified a high incidence of PAD in HD patients [14].…”
Section: Introductionmentioning
confidence: 98%
“…The authors found an increased association of CVD and mortality in diabetic patients with FU in comparison to those without FU. Interestingly, a recent study advocated a higher incidence of risk factors (PAD and peripheral neuropathy) for FU among HD patients [13]. In Qatar, an earlier report from our center identified a high incidence of PAD in HD patients [14].…”
Section: Introductionmentioning
confidence: 98%
“…All ulcers were included, because every ulcer should be recognized and treated to prevent escalation. [8][9][10]30 Another explanation could be that our data come forth of prospective clinical research instead of retrospective data, leading to a higher prevalence. Almost 70% of patients had a history of tobacco use and could cause the high prevalence.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of foot ulcers in our study is high (31.8% vs. 8%). 8,10 In this study also ulcerations without exudate production, in which the overlying skin was not intact, were included. This distinction is not mentioned in other literature, which could explain the high prevalence of foot ulcers in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialysis treatment is an independent risk factor for ulceration and amputation of the foot (Ndip et al 2010) and it has been shown that dialysis is associated with a threefold increase in the development of foot ulcers compared with a population of those with diabetes, not on dialysis (Jones et al 2012). It is not uncommon to see patients undergoing dialysis with bandaged or amputated feet.…”
Section: B I O D a T Amentioning
confidence: 99%